Investigation of inflammatory responses following the use of novel anisotropic hydrogel tissue expander in the skin of maxillofacial region / Kholoud Mohamed Ali Salim Igdayir - Kholoud Mohamed Ali, Salim Igdayir (2020)
Background: The purpose of tissue expander is to grow healthy supplementary tissue under the controlled of mechanical force exerted by the tissue expander. In the field of reconstructive and plastic surgery, the use of soft tissue expanders are important for growing healthy supplementary tissue. However, the molecular mechanism associated with the inflammatory response associated with the force generated from the use of tissue expanders is still not characterized. Among the many types of tissue expanders, anisotropic type of hydrogel tissue expander was chosen due to its ability to produce controlled incremental inflation on the tissue that enhance cellular adaptation and the ability of the cells to resist mechanical injury. Objective: To determine whether anisotropic hydrogel tissue expander promotes subclinical inflammatory response by triggering the secretion of pro-inflammatory cytokines. Material and Methods: Seven, 8 weeks old Sprague Dawley rats (300g ± 50g) were used as models. The rats were randomly divided into two groups: control group (n=3) and expanded group (n=4). The expanders were implanted subcutaneously at the forehead region for 28 days and surgically removed. The rats were sacrificed and skin samples were harvested and stored in 10% formaldehyde, fixed in formalin, and embedded in paraffin wax for histological investigation. Hematoxylin and eosin staining was performed to detect histological changes between the two groups and to detect the presence of an inflammatory response in the expanded samples. Moreover, the expression level of proinflammatory cytokines IL-1, TNF-α, IL-8, and IL-6 were determined by immunohistochemistry. Immune positivity was detected using secondary antibody conjugated with horseradish peroxidase (HRP) after staining with diaminobenzidine tetrahydrochloride (DAB). Results: Histological analysis showed no inflammatory response was present in the expanded tissue. There was no significant difference in cytokine production level between the expanded and control samples (p =0.071). iv However, there was very strong expression of IL-1 in the expanded tissue as 83 % of the cells were immune-positive compared to the controls. In contrast, there was no significant difference in IL-6, IL-8, and TNF-α production. A negative non-significant correlation between IL-1 immune-positive cells and the inflammatory cells in the expanded tissue was observed with a Spearman’s correlation coefficient of r= -0.500, p=0.667. Conclusion: The in vivo experiment revealed a high biocompatibility of the anisotropic self-inflating hydrogel tissue expander and no significant immunological or inflammatory reaction were observed between the control and tissue expanded groups.